1982
DOI: 10.1002/bimj.4710240404
|View full text |Cite
|
Sign up to set email alerts
|

How Large is the Probability for the Estimate of a Variance Component to be Negative?

Abstract: For a balanced one-way classification, where the normally dietributed observations obey a random model y t i = p + b i +cij with two variance components var (if) =uf and var (?ij) =u$, the probability is given that the analysis of variance estimate of ui will be negative. This probability depends on o:/uf and the degrees of freedom in the ANOVA table. Tables for this probability are given. If the normally distributed observations obey an intra-class correlation model, the probability that the Mean Square betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Laidig et al (2008) reported a fivefold larger ratio (14.2 compared with 14.4, a ratio of 1:1) from German long-term data on cultivar evaluation trials in wheat. The current simulation study showed that increasing the ratio of genotype VC to error VC decreased the REML-based bias of the genotype VC, and thus is in line with van Tassel et al (1995) and Verdooren (1982). Furthermore, it decreases the probability that the genotype VC is bounded at zero.…”
Section: Crop Sciencesupporting
confidence: 90%
“…Laidig et al (2008) reported a fivefold larger ratio (14.2 compared with 14.4, a ratio of 1:1) from German long-term data on cultivar evaluation trials in wheat. The current simulation study showed that increasing the ratio of genotype VC to error VC decreased the REML-based bias of the genotype VC, and thus is in line with van Tassel et al (1995) and Verdooren (1982). Furthermore, it decreases the probability that the genotype VC is bounded at zero.…”
Section: Crop Sciencesupporting
confidence: 90%
“…For selected models, under the Normality assumption, some exact tests and procedures for constructing confidence intervals are available, see SEELY and EL-BASSIOUNI (1983), HARVILLE and FENECH (1985), KHURI and LITTELL (1987) and VERDOOREN (1988). Nesting is generally a favourable feature.…”
Section: Componenrs Of Variancementioning
confidence: 99%
“…Negative variance components should therefore be allowed only with balanced data (Spilke, Hu, & Piepho, ). The probability of a negative variance estimate due to chance variation alone can be quite large in small data sets (Verdooren, ).…”
Section: Mixed Model Analysis Of Example 1 By Remlmentioning
confidence: 99%